Effect of earthworms on the community structure of active methanotrophic bacteria in a landfill cover soil. - Héry, M; Singer, A; Kumaresan, D; Bodrossy, L; Stralis-Pavese, N; Prosser, J; Thompson, I; Murrell, J (2008)
In the United Kingdom, landfills are the primary anthropogenic source of methane emissions. Methanotrophic bacteria present in landfill biocovers can significantly reduce methane emissions via their capacity to oxidize up to 100% of the methane produced. Several biotic and abiotic parameters regulate methane oxidation in soil, such as oxygen, moisture, methane concentration and temperature. Earthworm-mediated bioturbation has been linked to an increase in methanotrophy in a landfill biocover soil (AC Singer et al., unpublished), but the mechanism of this trophic interaction remains unclear. The aims of this study were to determine the composition of the active methanotroph community and to investigate the interactions between earthworms and bacteria in this landfill biocover soil where the methane oxidation activity was significantly increased by the earthworms. Soil microcosms were incubated with 13C-CH4 and with or without earthworms. DNA and RNA were extracted to characterize the soil bacterial communities, with a particular emphasis on methanotroph populations, using phylogenetic (16S ribosomal RNA) and functional methane monooxygenase (pmoA and mmoX) gene probes, coupled with denaturing gradient-gel electrophoresis, clone libraries and pmoA microarray analyses. Stable isotope probing (SIP) using 13C-CH4 substrate allowed us to link microbial function with identity of bacteria via selective recovery of 'heavy' 13C-labelled DNA or RNA and to assess the effect of earthworms on the active methanotroph populations. Both types I and II methanotrophs actively oxidized methane in the landfill soil studied. Results suggested that the earthworm-mediated increase in methane oxidation rate in the landfill soil was more likely to be due to the stimulation of bacterial growth or activity than to substantial shifts in the methanotroph community structure. A Bacteroidetes-related bacterium was identified only in the active bacterial community of earthworm-incubated soil but its capacity to actually oxidize methane has to be proven.